Influence of Imagery Training on Adjusting the Pressure of Fin Swimmers, Improving Sports Performance and Stabilizing Psychological Quality - Hsiao-Hsien Lin (MDPI AG, 2021)
This study analyzed the effects of imagery training on athletes’ imagery ability, physical anxiety and athletic performance. This study employed a mixed research approach. Snowball sampling was used to select 55 fin swimmers with imagery training experience and formal competition participation. Basic statistics were obtained, and Pearson product-moment correlation coefficient (PPMCC) analysis was performed using IBM SPSS Statistics for Windows, Version 26.0, and the results were compared with the opinions of three experts and were tested using multivariate validation methods. The results revealed that although imagery training can help athletes improve their performance and significantly reduce their anxiety during the competition, athletes can still make mistakes due to internal and environmental factors and even have negative thoughts that lead to their reduced likelihood of competition participation. By strengthening strategic and technical imagery training, we can help our fin swimmers perform at a higher level, achieve their goals, and improve overall satisfaction with their competition process and performance.